2013
DOI: 10.1111/j.1755-3768.2013.t037.x
|View full text |Cite
|
Sign up to set email alerts
|

24‐hour intraocular pressure rhythm in young healthy subjects evaluated with continuous monitoring using contact lens sensor

Abstract: Purpose To evaluate 24‐h intraocular pressure (IOP) rhythm reproducibility during repeated continuous 24‐h IOP monitoring with non‐contact tonometry (NCT) and a contact lens sensor (CLS) in healthy subjects. Methods Twelve young healthy subjects were housed in a sleep laboratory and underwent four 24‐h sessions of IOP measurements over a 6‐month period. After randomized attribution, the IOP of the first eye was continuously monitored using the CLS Sensimed TriggerFish® and the IOP of the fellow eye was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 0 publications
1
40
1
Order By: Relevance
“…Although the CLS does not measure IOP directly, it is hypothesized that it measures a composite of IOP and volume changes as well as the effect of ocular biomechanical properties on these parameters. 4,16,22 Our results showed that topical administration of a prostaglandin analogue, but not of other classes of medications, reduced the nocturnal IOP rise that accompanies the change in body position when individuals go to sleep. Overall, however, ocular hypotensive medications did not seem to produce a change in circadian IOP-related patterns.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although the CLS does not measure IOP directly, it is hypothesized that it measures a composite of IOP and volume changes as well as the effect of ocular biomechanical properties on these parameters. 4,16,22 Our results showed that topical administration of a prostaglandin analogue, but not of other classes of medications, reduced the nocturnal IOP rise that accompanies the change in body position when individuals go to sleep. Overall, however, ocular hypotensive medications did not seem to produce a change in circadian IOP-related patterns.…”
Section: Discussionmentioning
confidence: 66%
“…14 Non-invasive and ambulatory continuous 24-h monitoring of IOP-related patterns has recently become possible with the introduction of a contact lens sensor (CLS). [15][16][17][18] The CLS measures changes in IOP indirectly through registration of ocular dimensional changes. The purpose of this study was to investigate, under near-physiological conditions, changes in 24-h IOP-related profiles in patients undergoing IOP-lowering monotherapy and adjunctive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements given by the Triggerfish lens device (Sensimed, Lausanne, Switzerland) have not corresponded to the IOP measured in mmHg and also can be influenced by biomechanics of the cornea such as corneal curvature, central cornea thickness and hysteresis. 62 Some side effects such as corneal oedema, hyperemia and discomfort have also been associated with its use. Meanwhile, the WDT is reproducible and shows clinically relevant results validated several times by a series of peer-reviewed studies; it can be an important tool for IOP profile assessment in glaucoma management.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] This may result in patients having their peak IOP outside clinic hours. With continuous 24-h IOP monitoring being impractical, even with newer technologies, 10,11 challenge tests including the water drinking test (WDT) and supine test (ST) have been a popular alternative to derive these parameters. 12,13 Despite the clinical potential of the WDT and ST, quantitative analysis of each one is scarce regarding their corresponding IOP values.…”
Section: Introductionmentioning
confidence: 99%